Penggunaan Qris Pada UMKM: Tinjauan Kajian Literasi, Layanan Dan Preferensi Pengguna. - Marshella, Ayu; Burhan, Aditya (Gorontalo State University, 2026)
This study aims to analyze the factors influencing the decision to use QRIS (Quick Response Code Indonesian Standard) in transactions among Micro, Small, and Medium Enterprises (UMKM), The variables examined include financial literacy, service quality, lifestyle, security, and ease of use. A quantitative approach was employed using a survey method through the distribution of questionnaires to 199 QRIS users within the UMKM sector in Jakarta. Data were analyzed using multiple linear regression to identify the influence of each variable. The results indicate that lifestyle, security, and ease of use have a positive and significant affect on the decision to use QRIS, while financial literacy and service quality do not show a significant influence. These findings suggest that an understanding of the digital lifestyle as well as perceptions of security and technological convenience are key determinants in driving QRIS adoption among UMKM. The implications of this study highlight the importance of digital lifestyle education and enhancing security features to encourage broader QRIS usage within the UMKM sector.